Deterministic algorithm for selective shunt active power compensators according to IEEE Std. 1459 (2017)
ABSTRACT: This paper proposes a deterministic algorithm to scale the reference currents of a shunt active power compensator (SAPC) based on IEEE Std. 1459 power decomposition when SAPC maximum output compensating current is going to be exceeded. The selective SAPC is proposed to improve power quality and energy efficiency in power networks by means of the cancelation or reduction of the non-efficient powers (Q1+, SU1, SeN). The non-efficient powers can be reduced in six possible sequences according to the priority of compensation. When SAPC maximum output current capacity is exceeded, the proposed algorithm limits the SAPC output compensating currents and the non-efficient currents can only be partially reduced in the power network. The reduction of the non-efficient powers depends on the selected compensation sequence. Experimental results for several compensation sequences demonstrate the appropriate operation of the selective SAPC using the proposed scaling algorithm.